Mitochondrial Dysfunction in the Cardio-Renal Axis - Méndez Barbero, Nerea; Oller, Jorge; Sanz, Ana B.; Ramos, Adrian M.; Ortiz, Alberto; Ruiz Ortega, Marta; Rayego Mateos, Sandra (My University, 2023)
Abstract: Cardiovascular disease (CVD) frequently complicates chronic kidney disease (CKD). The risk of all-cause mortality increases from 20% to 500% in patients who suffer both conditions; this is referred to as the so-called cardio-renal syndrome (CRS). Preclinical studies have described the key role of mitochondrial dysfunction in cardiovascular and renal diseases, suggesting that maintaining mitochondrial homeostasis is a promising therapeutic strategy for CRS. In this review, we explore the malfunction of mitochondrial homeostasis (mitochondrial biogenesis, dynamics, oxidative stress, and mitophagy) and how it contributes to the development and progression of the main vascular pathologies that could be affected by kidney injury and vice versa, and how this knowledge may guide the development of novel therapeutic strategies in CRS. Keywords: mitochondrial dysfunction; kidney disease; cardiovascular disease; oxidative stress; treatment